2021
DOI: 10.1016/j.celrep.2021.108957
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas aeruginosa T6SS-mediated molybdate transport contributes to bacterial competition during anaerobiosis

Abstract: Highlights d H2-T6SS mediates molybdate acquisition by secretion of ModA d Expression of H2-T6SS is activated by the master regulator Anr and anaerobiosis d ModA interacts with the outer membrane protein IcmP and uses it to deliver molybdate d The T6SS-ModA-IcmP system plays a role for P. aeruginosa

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
58
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(66 citation statements)
references
References 49 publications
5
58
0
Order By: Relevance
“…In P. aeruginosa T6SS has been shown to react to stress induced by subinhibitory concentrations of antibiotics such as kanamycin or polymyxins ( Jones et al, 2013 ; Vitale et al, 2020 ). Additionally, P. aeruginosa T6SS facilitates the uptake of molybdate and increases its competitiveness ( Wang et al, 2021 ). Our results showed that the expression of P. phymatum T6SS was not influenced by the presence of subinhibitory and inhibitory concentrations of several tested antibiotics, at least not at the transcriptional level (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…In P. aeruginosa T6SS has been shown to react to stress induced by subinhibitory concentrations of antibiotics such as kanamycin or polymyxins ( Jones et al, 2013 ; Vitale et al, 2020 ). Additionally, P. aeruginosa T6SS facilitates the uptake of molybdate and increases its competitiveness ( Wang et al, 2021 ). Our results showed that the expression of P. phymatum T6SS was not influenced by the presence of subinhibitory and inhibitory concentrations of several tested antibiotics, at least not at the transcriptional level (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Like the previously discovered two H1-T6SS effectors Tse1 and Tse3, which can hydrolyze peptidoglycan and provide a competitive fitness advantage (Russell et al, 2011), H2-T6SS improves bacterial competition by promoting molybdate (MoO 4 2− ) acquisition under anaerobic conditions (Wang et al, 2021). As a transcriptional regulator, Anr can activate H2-T6SS expression under anaerobic conditions (Wang et al, 2021). Anr in P. aeruginosa controls the switch from aerobic to anaerobic growth and plays a pivotal role in adapting to microaerobic or anoxic conditions (Ugidos et al, 2008;Tata et al, 2017).…”
Section: Molybdenummentioning
confidence: 95%
“…In P. aeruginosa, the H2-T6SS secreted ModA has been identified as a molybdate-binding protein and mediated molybdate acquisition. Moreover, a ModA partner that participates in molybdate transport has also been identified as IcmP that is an insulin-cleaving metalloproteinase outer membrane protein (Wang et al, 2021). The T6SS-ModA-IcmP system contributes to bacterial virulence and participates in bacterial competition under anaerobic conditions.…”
Section: Molybdenummentioning
confidence: 99%
See 2 more Smart Citations